Novel treatment strategy with radiofrequency ablation and surgery for pregnant patients with hepatocellular carcinoma: a case report - Megumi Matsuo; Katsunori Furukawa; Hiroaki Shimizu; Hideyuki Yoshitomi; Tsukasa Takayashiki; Satoshi Kuboki; Shigetsugu Takano; Daisuke Suzuki; Nozomu Sakai; Shingo Kagawa; Hiroyuki Nojima; Masayuki Ohsuka (Surgical Case Reports)
Abstract Background Hepatocellular carcinoma (HCC) during pregnancy is rare, with a poor prognosis. Recently, however, increasing resection rates have improved survival rate. Currently, various surgeries are safely performed after the second trimester and termination of pregnancy is not always necessary. However, surgery is sometimes limited by gestational age or the patient’s will. When patients with HCC refuse surgery during pregnancy, we face specific problems with respect to curability and fetal life. Meanwhile, previous studies have revealed radiofrequency ablation (RFA) as a possible alternative to surgery for the treatment of early HCC and shown its favorable local control rate for advanced HCC. However, no case of HCC treated with RFA during pregnancy has yet been reported. Case presentation Here, we present the case of a 33-year-old woman, who was a hepatitis B virus carrier. The patient had been followed up because HBV carrier could develop hepatitis or HCC. And she was diagnosed with a 40-mm HCC tumor at 17 weeks of gestation. She refused surgery because she was pregnant and wanted to continue her pregnancy; therefore, we performed RFA for the local control of her HCC at 17 weeks of gestation and radical surgery at postpartum. She delivered a healthy baby and has survived without recurrence for 6 years after the surgery. Conclusions Surgery is potentially a curative treatment for HCC whether the patient is pregnant or not. However, various problems unique to pregnancy make it difficult to perform a straightforward surgery. Our case revealed that RFA can be safely performed in pregnant patients during the second trimester, and the combination of RFA and surgery can radically increase the resection rate of HCC during pregnancy.